2019
DOI: 10.1021/acssuschemeng.9b00260
|View full text |Cite
|
Sign up to set email alerts
|

Green and Controllable Synthesis of Au–Ag Bimetal Nanoparticles by Xylan for Surface-Enhanced Raman Scattering

Abstract: In surface-enhanced Raman scattering, Ag nanoparticles are broadly employed. However, their lack of oxidation resistance means that their performance diminishes and is difficult to repeat. In this study, with addition of xylan, Au–Ag core–shell and alloy nanoparticles were prepared. Besides functioning as a reducing and stabilizing agent for Au–Ag bimetal nanoparticles, xylan protected them from oxidation and aggregation and created hot spots between interconnected nanoparticles. By seed-mediated methods, Au–A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 34 publications
(50 reference statements)
1
15
0
Order By: Relevance
“…R6G exhibited an electronic absorption maximum at 530 nm that matched the laser excitation wavelength and also lay close to the SPR of Cu NPs, and so RR effects were expected to be observed for both the bulk solid and adsorbed molecules in our study using a 532-nm laser excitation. As observed by previous researchers, the SERRS effect on Au nanoparticles or roughened Cu surfaces resulted in the appearance of the characteristic Raman peaks of the adsorbed molecules using red (632.8 nm) to blue (488 nm) excitation lines [83,84]. Our data show that the spectrum could be detected down to at least 10 −6 M, where the relative intensities were comparable to those of the bulk solid (Figure 6c).…”
Section: Sers/serrs Activity Of Analytes On Cu/gcn Hybrid Support Produced Using Pulsed Laser Depositionsupporting
confidence: 88%
See 1 more Smart Citation
“…R6G exhibited an electronic absorption maximum at 530 nm that matched the laser excitation wavelength and also lay close to the SPR of Cu NPs, and so RR effects were expected to be observed for both the bulk solid and adsorbed molecules in our study using a 532-nm laser excitation. As observed by previous researchers, the SERRS effect on Au nanoparticles or roughened Cu surfaces resulted in the appearance of the characteristic Raman peaks of the adsorbed molecules using red (632.8 nm) to blue (488 nm) excitation lines [83,84]. Our data show that the spectrum could be detected down to at least 10 −6 M, where the relative intensities were comparable to those of the bulk solid (Figure 6c).…”
Section: Sers/serrs Activity Of Analytes On Cu/gcn Hybrid Support Produced Using Pulsed Laser Depositionsupporting
confidence: 88%
“…These SERS performances were explained by the fact that the xylan capping allowed creating hotspots between Au/Ag nanoparticles. Optimal SERS performances for xylan-capped Au/Ag nanoparticles were realized for a mole ratio of AgNO 3 to HAuCl 4 equal to 4 and a dosage of xylan equal to 1 in the fabrication of Ag shell corresponding to 2.86 × 10 −8 mol of xylan (see Figure 3) [84]. To conclude this section on bimetallic nanosystems, Prakash et al reported on the SERS detection of bacteria by using Au/Ag plasmonic nanoparticles which were positively charged (see Figure 4).…”
Section: Bimetallic Nanoparticles For Sers Sensingmentioning
confidence: 99%
“…Compared with BP, the BP@Au composite exhibits four significant peaks at 38.2°, 44.3°, 64.7°and 77.5° and can be assigned to the (111), (200), (220) and (311) Au planes (JCPDS 04‐0784), [30] respectively, confirming that Au nanoparticles are successfully anchored on the surface of BP nanosheets. As against BP@Au, the intensity of the diffraction peaks in BP@Au−Ag nanohybrids is slightly increased, [31] indicating the formation of Ag−Au bimetallic nanoparticles over the BP matrix.…”
Section: Resultsmentioning
confidence: 98%
“…These SERS performances were explained by the fact that the xylan capping allowed creating hotspots between Au/Ag nanoparticles. Optimal SERS performances for xylan-capped Au/Ag nanoparticles were realized for a mole ratio of AgNO 3 to HAuCl 4 equal to 4 and a dosage of xylan equal to 1 in the fabrication of Ag shell corresponding to 2.86 × 10 −8 mol of xylan (see Figure 3 ) [ 84 ].…”
Section: Novelties On Plasmonic and Non-plasmonic Nanomaterials Fomentioning
confidence: 99%
“…SERS spectra of ( c ) 4-MBA molecules and ( d ) Sudan I molecules for different concentrations obtained with optimized xylan-capped Au/Ag nanoparticles of ( b ). All the figures are reprinted (adapted) with permission from [ 84 ], Copyright 2019 American Chemical Society.…”
Section: Figurementioning
confidence: 99%